Psychometric properties of the Alcohol Use Disorders Identification Test (AUDIT) across cross-cultural subgroups, genders, and sexual orientations: Findings from the International Sex Survey (ISS) - Zsolt Horváth; Léna Nagy; Mónika Koós; Shane W. Kraus; Zsolt Demetrovics; Marc N. Potenza; Rafael Ballester-Arnal; Dominik Batthyány; Sophie Bergeron; Joël Billieux; Peer Briken; Julius Burkauskas; et al. (Comprehensive Psychiatry, 2023)
Introduction: Despite being a widely used screening questionnaire, there is no consensus on the most appropriate measurement model for the Alcohol Use Disorders Identification Test (AUDIT). Furthermore, there have been limited studies on its measurement invariance across cross-cultural subgroups, genders, and sexual orientations. Aims: The present study aimed to examine the fit of different measurement models for the AUDIT and its measurement invariance across a wide range of subgroups by country, language, gender, and sexual orientation. Methods: Responses concerning past-year alcohol use from the participants of the cross-sectional International Sex Survey were considered (N = 62,943; Mage: 32.73; SD = 12.59). Confirmatory factor analysis, as well as measurement invariance tests were performed for 21 countries, 14 languages, three genders, and four sexual-orientation subgroups that met the minimum sample size requirement for inclusion in these analyses. Results: A two-factor model with factors describing ‘alcohol use’ (items 1–3) and ‘alcohol problems’ (items 4–10) showed the best model fit across countries, languages, genders, and sexual orientations. For the former two, scalar and latent mean levels of invariance were reached considering different criteria. For gender and sexual orientation, a latent mean level of invariance was reached. Conclusions: In line with the two-factor model, the calculation of separate alcohol-use and alcohol-problem scores is recommended when using the AUDIT. The high levels of measurement invariance achieved for the AUDIT support its use in cross-cultural research, capable also of meaningful comparisons among genders and sexual orientations.